Use of Topical Corticosteroids in the Treatment of Noninfectious Inflammatory Dermatoses of the Scalp: A Survey of Practicing Dermatologists and Dermatology Residents Using Delphi Methodology - Mir-Bonafé JF; Piquero-Casals J; Prudkin L; Delgado J; Santamaria Martínez J; Garcia-Patos Briones V (Clinical, Cosmetic and Investigational Dermatology, 2024)
Juan Francisco Mir-Bonafé,1 Jaime Piquero-Casals,2 Ludmila Prudkin,3 Jesus Delgado,3 Julia Santamaria Martínez,3 Vicente Garcia-Patos Briones4 1Department of Dermatology, Hospital Son Llàtzer, Palma de Mallorca, Spain; 2Department of Aesthetic Dermatology and Laser, Dermik, Clínica Dermatológica Multidisciplinar, Barcelona, Spain; 3Innovation and Development, ISDIN, Barcelona, Spain; 4Department of Dermatology, Hospital Vall d’Hebron, Barcelona, SpainCorrespondence: Jaime Piquero-Casals, Department of Aesthetic Dermatology and Laser, Dermik, Clínica Dermatológica Multidisciplinar, Barcelona, Spain, Tel +34 935464710, Email j.piquero@dermik.esBackground: Noninfectious inflammatory dermatoses of the scalp are common, and their symptomsin particular, those affecting appearance, can have a psychological effect that may be disproportionate to their clinical severity. Effective, cosmetically acceptable treatments are important to manage these conditions. Topical corticosteroids form the cornerstone of acute treatment for many of these conditions. We surveyed practicing dermatologists and dermatology residents to determine the current clinical practice in prescribing topical corticosteroids for these disorders in their various preparation formats.Methods: A Delphi method was used, consisting of 2 questionnaire rounds. The first round contained 34 questions and was completed by 612 dermatologists and dermatology residents via email. The first round of responses was analyzed, and points that had >  70% agreement were used to form a second questionnaire of 21 statements. This second round was completed by 346 participants, and their responses were used to generate a final report. Participants were practicing in both public and private practices.Results: Clobetasol propionate 0.05% topical solution was considered to be the most appropriate treatment for noninfectious inflammatory scalp dermatoses in general, with 75.1% agreement in the second round of questionnaire. The main advantages of clobetasol propionate over other topical corticosteroids were reported as potency, effectiveness, and broad action spectrum (94.8% agreement). The preferred pharmaceutical format was the solution of clobetasol propionate.Conclusion: Clobetasol propionate was the preferred topical treatment for the management of scalp dermatoses, usually as first-line treatment; solution was the preferred preparation.Keywords: seborrheic dermatitis, psoriasis, shampoo, topical, solution, clobetasol, scalp, therapy